2015
DOI: 10.7314/apjcp.2015.16.13.5477
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prethrombotic States in Patients with Malignant Tumors

Abstract: Background: This study aimed to investigate the incidence and risk factors for a prethrombotic state in patients with malignant tumors. Materials and Methods: Plasma d-dimer (D-D) in patients with malignant tumors was measured. Abnormal rates of D-D and possible risk factors like gender, age, type of tumor, and staging of tumor were analyzed. Results: Of 1,453 patients, 629 demonstrated plasma D-D abnormality (43.3%).The D-D abnormal rate of male patients (n=851, 43.5%) was not statistically significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Activated coagulation in cancer patients is implicated both in tumor progression and in development of VTE . While several studies have linked activated coagulation with many different cancer types, there are only few publications in malignant melanoma . To our knowledge, this is the first large‐scale cohort study examining the association between coagulation and survival in malignant melanoma patients.…”
Section: Discussionmentioning
confidence: 94%
“…Activated coagulation in cancer patients is implicated both in tumor progression and in development of VTE . While several studies have linked activated coagulation with many different cancer types, there are only few publications in malignant melanoma . To our knowledge, this is the first large‐scale cohort study examining the association between coagulation and survival in malignant melanoma patients.…”
Section: Discussionmentioning
confidence: 94%
“…Tumors have been reported to induce the inflammatory response, release cytokines, and injure vascular walls directly or indirectly by releasing tissue factor, which can activate the coagulation cascade and cause coagulation dysfunction. 30 Cancer patients have been shown to have a significantly higher D-dimer level than that of healthy controls 31 in situations of enhanced fibrin formation and fibrinolysis. Moreover, the D-dimer level has been reported to be not only an adverse prognostic factor but also a biomarker for the response to chemotherapy in several types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical and laboratory findings indicate that 90% of all metastatic cancers are accompanied by abnormalities in coagulation variables, for example, circulating D -dimers, thrombin–antithrombin complexes, tissue factor (TF), and other changes. [ 6 ] Cui et al [ 7 ] have shown that tumor cells could impair the balance of coagulation, anticoagulant, and fibrinolytic system through multiple mechanisms, which leads to prethrombotic state. Therefore, cancer patients are vulnerable to stroke.…”
Section: Discussionmentioning
confidence: 99%